Identification of Gene Encoding Plasmodium knowlesi Phosphatidylserine Decarboxylase by Genetic Complementation in Yeast and Characterization of in Vitro Maturation of Encoded Enzyme - Choi, Jae-Yeon (American Society for Biochemistry and Molecular Biology, 2012)
The 23-megabase genome of Plasmodium falciparum, the causative agent of severe human malaria, contains ∼5300 genes, most of unknown function or lacking homologs in other organisms. Identification of these gene functions will help in the discovery of novel targets for the development of antimalarial drugs and vaccines. The P. falciparum genome is unusually A + T-rich, which hampers cloning and expressing these genes in heterologous systems for functional analysis. The large repertoire of genetic tools available for Saccharomyces cerevisiae makes this yeast an ideal system for large scale functional complementation analyses of parasite genes. Here, we report the construction of a cDNA library from P. knowlesi, which has a lower A + T content compared with P. falciparum. This library was applied in a yeast complementation assay to identify malaria genes involved in the decarboxylation of phosphatidylserine. Transformation of a psd1Δpsd2Δdpl1Δ yeast strain, defective in phosphatidylethanolamine synthesis, with the P. knowlesi library led to identification of a new parasite phosphatidylserine decarboxylase (PkPSD). Unlike phosphatidylserine decarboxylase enzymes from other eukaryotes that are tightly associated with membranes, the PkPSD enzyme expressed in yeast was equally distributed between membrane and soluble fractions. In vitro studies reveal that truncated forms of PkPSD are soluble and undergo auto-endoproteolytic maturation in a phosphatidylserine-dependent reaction that is inhibited by other anionic phospholipids. This study defines a new system for probing the function of Plasmodium genes by library-based genetic complementation and its usefulness in revealing new biochemical properties of encoded proteins.